Crystal Growth Study of CoZnPO-HEX (CZP) Synthesised using Solvent-Free Method and Its Crystal Growth Simulation - Farida, Nani; Ningtyas, Anggraini Widya; Pertiwi, Elva Oktavianti; Wijaya, Husni Wahyu; Danar, Danar; Sari, Meyga Evi Ferama (Akta Kimia Indonesia, 2024)
Zinco-phosphate having CZP structure (CoZnPO-HEX) has a potential as a catalyst in Knoevenagel condensation of benzaldehyde with activated methylenic compounds or the Michael addition of nitroethane to olefin. The potency is led by the physicochemical properties of the material, which depend on its crystal habits. Understanding the crystal growth of materials is important to be able to design and control their crystal habits.  Therefore, the crystal growth study of CoZnPO-HEX is crucial for its crystal habit modification as well as for optimization and expansion of the material’s functions. Several parameters of crystal growth, such as nucleation time, gel supersaturation, and crystal size changes during the synthesis process can be analysed by observing the material’s crystallisation profile. In this study, crystallisation analysis was performed on CoZnPO-HEX, synthesised using solvent-free method, from its crystallinity curve based on Powder-XRD data supported by SEM data. As a comparison, crystal growth simulation was performed using CrystalGrower program to determine the morphology, surface topography, and theoretical crystal growth mechanisms. From this study, we found that the nucleation time of the CoZnPO-HEX crystals prepared using a solvent-free method took place during the precursor grinding process at room temperature. The crystal morphology of the as-prepared materials agrees well with the simulation’s one. Moreover, the CrystalGrower simulation proved that the smallest t-czp-1 tile started the nucleation on the crystal surface because of its low free energy.